2020
DOI: 10.1088/2053-1591/ab621e
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of polymer-based nanocomposites microwave absorption performance in X–band

Abstract: The present work focused on electromagnetic (EM) absorption performance comparison of different polymer nanocomposite structures. Synthesis and fabrication of polymer nanocomposite composed of graphene, polyurethane (PU), epoxy was done using in situ polymerization and resin transfer moulding respectively. The effect of polymer on EM properties of composite was carried out using waveguide measurement technique in X-band. Reflection Loss (RL) and shielding effectiveness (SE) were measured for various nanocompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…By correlating with SEM analysis and previous reports with the present study, the composites with 5% level with PEC have better performance as electromagnetic absorbing properties and agglomeration process at 7% CNT level for composites. Thus, this characteristic suggests the formation of an interconnection network with CNT and PEC in the composites, which promotes better electrical and dielectric losses (Su et al, 2012;De Rosa et al, 2010;Santhosi et al, 2019Santhosi et al, , 2020.…”
Section: Microwave Absorbing Performancementioning
confidence: 97%
See 1 more Smart Citation
“…By correlating with SEM analysis and previous reports with the present study, the composites with 5% level with PEC have better performance as electromagnetic absorbing properties and agglomeration process at 7% CNT level for composites. Thus, this characteristic suggests the formation of an interconnection network with CNT and PEC in the composites, which promotes better electrical and dielectric losses (Su et al, 2012;De Rosa et al, 2010;Santhosi et al, 2019Santhosi et al, , 2020.…”
Section: Microwave Absorbing Performancementioning
confidence: 97%
“…The maximum absorption reaches À43.56 dB when the concentration of CNT is 5% and reduced to À19.42 dB when the concentration increased to 7%. Due to the agglomeration of CNT in the epoxy resin, Figure 6 as shown in Table 1 SEM analysis about the agglomeration effect (Su et al, 2012;De Rosa et al, 2010;Santhosi et al, 2019Santhosi et al, , 2020.…”
Section: Microwave Absorbing Performancementioning
confidence: 99%
“…Recently, polyurethane/graphene composites have been attracting much attention in microwave absorption and electromagnetic shielding. 134–151 Santhosi et al 134 observed the R L value of −35 dB at 12.1 GHz and SE value of −45 dB in PU/epoxy reinforced with 2.5 wt% of graphene. In another work, epoxy-encapsulated PU/graphene (2.5–4.2 wt%) showed EMI SE in the range of 30–61 dB in the X band.…”
Section: Carbonaceous Nanomaterials/polymer Nanocompositesmentioning
confidence: 98%
“…4 Accordingly, the EMI shielding properties of nanocarbon incorporated in polymethylmethacrylate (PMMA), polystyrene (PS), epoxy resin (ER), polypropylene (PP), polyurethane (PU), polyvinylalcohol (PVA), polydimethylsiloxane (PDMS), polyimide (PI), polyethylene (PE), natural rubber (NR) and few other polymers are reviewed below. 66–213…”
Section: Carbonaceous Nanomaterials/polymer Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation